Aviation, Space or Aerospace? Exploring the knowledge networks of two industries in den Netherlands. - Tom Broekel; Ron Boschma (Philipps-University Marburg, Department of Geography, 2010)
Little effort has been made to identify industries' knowledge networks, and to what extent knowledge relations occur between actors in different industries. This paper presents a network study on the Dutch aviation and space industry. Both industries are often treated as similar and categorized as aerospace accordingly, although they tend to rely on different knowledge bases. Our study shows that the structure of the knowledge networks differs between the two industries, and few knowledge linkages have been established between the two. Our findings also suggest that the gap between the two industries' knowledge networks is more pronounced for market knowledge than for technological knowledge. Non-profit organizations do seem to bridge the knowledge networks of the two industries.
Keywords: R11; R12; O18; O33; 330; aerospace industry; knowledge base; knowledge network; bridging organization